The Role of POE Oriented Science Learning to Correct Misconception about Temperature Effect on Water Desity in Elementary Education - ZJ, Arminas; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Literacy ability is a fundamental thing that must be possessed by students in facing the global era to be able to meet the needs of life in various situations. Science literacy is the ability to understand science, communicate science, and apply the ability of science to solve problems. To improve the ability of scientific literacy in addition to requiring student motivation, teachers also need to consider learning strategies that are appropriate to the conditions and potential of students which in the learning process focuses on providing direct experience and the application of the nature of science. The science learning study oriented Predict, Observe, Explain (POE) aims to correct misconceptions in science subjects with the material the influence of temperature on the density of water in elementary education. One effort to improve science misconceptions is to change teacher centered learning into student centered learning. One learning strategy that actively involves students while still raising science characteristics is that students are able to develop the knowledge they have by using the POE (Predict-Obiserve-Explain) learning model which is expected to improve science misconceptions with temperature material that can affect the density of water in elementary education